METHOD OF AIR-CLIMATIC CONDITIONS FOGGING OF REGIONS FOR THE MAINTENANCE OF HIGHWAYS IN UNFAVORABLE CLIMATIC CONDITIONS - O‘roqov Aslidin Khushvaqtovich; Ibroimov Husan Ibodullayevich (Scholar Express Journal, 2021)
The article considers the issues of taking into account the influence of airclimatic factors in the maintenance, repair and operation of highways, airclimatic conditions of the regions of the Republic of Uzbekistan, taking into account the winter season. It was recognized that road zoning is an important and powerful method of systematization of information.
Keywords: Separation; climate; natural and climatic; highways